The mechanistic effects of acupuncture in rodent neurodegenerative disease models: a literature review - Li, Boxuan; Deng, Shizhe; Jiang, Hailun; Zhu, Weiming; Zhuo, Bifang; Du, Yuzheng; Meng, Zhihong (Frontiers in Neuroscience, 2024)
Neurodegenerative diseases refer to a battery of medical conditions that affect the survival and function of neurons in the brain, which are mainly presented with progressive loss of cognitive and/or motor function. Acupuncture showed benign effects in improving neurological deficits, especially on movement and cognitive function impairment. Here, we reviewed the therapeutic mechanisms of acupuncture at the neural circuit level in movement and cognition disorders, summarizing the influence of acupuncture in the dopaminergic system, glutamatergic system, γ-amino butyric acid-ergic (GABAergic) system, serotonergic system, cholinergic system, and glial cells at the circuit and synaptic levels. These findings can provide targets for clinical treatment and perspectives for further studies.